Implementation of Production Normalize DB based on Functional Dependency Table (FDT) - Maitham Ali Naji (Journal of Madenat Alelem University College, 2013)
This paper presents the result of previous papers. It is provides computerized technique to design and create normalize relational database based on Functional Dependency Table (FDT). The system use Data Access Object (DAO) to define tables to the table collection. After the tables and fields have been created, the system will define an index and primary key attributes to the first field of each table, finally the relationships type is created between tables depend on the primary keys and foreign keys.